Predicting Intention to Continue Using E-Tourism Technologies amidst Covid-19 Endemic: A PLS-SEM Approach - Luqman, Azyanee; Li, Cheam Chai; Mohamad, Siti Sarah (Information Management and Business Review, 2023)
After almost two years of stalling, the tourism sector is now thriving as we move into the Covid-19 endemic phase, making travel safer. Therefore, continuous use of personalized immersive technology that can deliver timely information and shield users from the outbreak is essential. This study looks at how travellers intend to continue using e-tourism technologies which include augmented reality, social media, smartphone apps, smart technologies, websites and reservation systems. Purposive sampling was used to select 200 respondents who were above 18 years old to participate in a survey that was based on the Expectation-Confirmation Model. The acquired data was then examined using PLS SEM for hypothesis testing. The results showed that satisfaction with e-tourism technologies was the most significant predictor of motivation to keep using such technologies. Further discussion includes contributions to the field of knowledge as well as for players, developers and service providers in the tourism sector.